PENGARUH INFLUENCER MARKETING DAN SALES PROMOTION TERHADAP MINAT BELI VIRTUAL ITEM DALAM GAME MOBILE LEGENDS DI PANGKALPINANG - Khali Jibran Ayasy (PT. Hasba Edukasi Mandiri, 2025)
Virtual items in Mobile Legends are increasingly in demand with the rise of online gaming. Marketing strategies such as influencer marketing and sales promotion are used to boost purchase intention, especially among active social media users. This study uses a descriptive quantitative approach with 160 respondents in Pangkalpinang City. The sampling technique was purposive sampling, and data were collected through an online questionnaire. Data were analyzed using multiple linear regression. The results show that influencer marketing has a positive and significant effect on purchase intention. Sales promotion also has a positive and significant effect. Simultaneously, both variables significantly influence purchase intention. This research contributes to digital marketing, especially in promotional strategies in the gaming industry. The results can be useful for game developers and marketers in designing more effective marketing strategies.